MENGUKUR MINAT BERWIRAUSAHA MAHASISWA POLITEKNIK NEGERI BENGKALIS DENGAN ADANYA PELAKSANAAN PROGRAM MAHASISWA BERWIRAUSAHA (PMW) - Dwi Astuti; Nazrantika Sunarto; Supriati Supriati (Inovbiz: Jurnal Inovasi Bisnis, 2020)
This study aims to determine how the students' interest in entrepreneurship, the most dominant interest in entrepreneurship among students, and the lowest interest in entrepreneurship among students of Bengkalis State Polytechnic. The population in this study were active students of Bengkalis State Polytechnic in 2019, with a sample size of 100 students, and the sampling technique used was proportionate stratified random sampling. The results showed that of the four indicators of entrepreneurial interest, namely feeling motivated, feeling interested, feeling happy, and having a desire to be entrepreneurial, the overall criteria are very high, the most dominant is feeling happy to be entrepreneurial with an average response of 4.64 , while the lowest was feeling motivated to become entrepreneurial with an average response rate of 4.21.